Chapter Illusionismo prospettico ed èkphrasis: dalla rappresentazione artistica all’espansione digitale - Gallo, Mara (FrancoAngeli, 2025)
The here collected contributions relating to the 46th International Conference of the Representation Disciplines Teachers, organized jointly by Sapienza University of Rome, Roma Tre University, and San Raffaele Roma University, aim to offer the scientific community a reflection on the theoretical and methodological aspects related to the concept of èkphrasis, a term that, in the field of representation, concerns descriptive, analogical, and digital activities that generate new knowledge in several areas of application. The Conference aims to place at the center of the discussion an interpretation of the concept of research that, without neglecting an idea of study, protection, and enhancement of environmental and cultural heritage, focuses on the needs of contemporary society and its possible developments, making use of innovative theoretical, methodological, and operational activities, including those characterized by an interdisciplinary approach. According to this interpretation, research can also be seen as a foreshadowing of the definition and testing of experimental proposals aimed at exploring new areas of investigation: this opens up imaginative and utopian perspectives in the relationship between the sciences, the arts, and the disciplines that contribute to common goals, through the experimentation of methods, techniques, and languages for conceiving, prefiguring, designing, and representing.